Attitude towards communication skills among undergraduate nursing students - Sharma, Sharada; Gurung , Bishnu; Kayastha, Srijana; Panta, Ganga (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: Effective communication is an important part of holistic nursing care that improves the patient’s satisfaction. The main aim of this study is to assess the attitude toward communication skills among undergraduate nursing students.Methods: Quantitative cross-sectional study conducted among 271 students studying in constituent nursing campuses of the Tribhuvan University, Institute of Medicine. A multistage sampling technique was used and information was collected using Communication Skills Attitudes Scale through Google Forms. The collected data was analyzed using SPSS. Student t-test and one way ANOVA were used to compare scores between groups of students.Results: The mean age of students was 24.1±3.3 years. Only 8.9% of students had taken communication skill training and 36.9% perceived language as the barrier to communication. The mean score for positive attitude was 49.5±4.8 and negative attitude was 33.6 ± 4.5 out of 65 with a total mean score of 87.2 ± 6.2. There was a significant difference in positive attitude with marital status and living arrangement (p